The roles of chaperonins in bacteria - Lund, Peter (Henry Stewart Talks, 2007)
The discovery of the GroEL chaperonin in E. coli, Organization of the GroEL and GroES genes, Oligomeric structure of GroEL and GroES proteins, Key roles of GroEL, The substrates of GroEL, Chaperonins in other bacteria and their roles
Archived at 2020/08/13